TEACHER UNDERSTANDING IN DATA COLLECTION TECHNIQUES FOR COUNSELING GUIDANCE IN LOWER CLASS SDN 2 TAKERANKLATING - Qibtiyah, Mar'atul; Afaf, Niswatin Nawal; Widyanti, Zurifah Nur; Mudayan, Arfian (Universitas Muhammadiyah Lamongan, 2024)
Analysis of teacher understanding in collecting guidance and counseling data in elementary schools is very important for educators in knowing the character and needs of students. This research aims to determine the level of understanding of elementary school teachers in data collection techniques for guidance and counseling in lower grades. This research uses descriptive qualitative methods. The instruments in the research used teacher interview techniques and teacher observation, while the subject was a lower grade elementary school teacher. The results of this research are (1) knowing the types of data in counseling guidance in elementary schools, (2) teachers conducting an analysis of student needs in lower grades, (3) showing that the level of understanding of elementary school teachers regarding techniques for collecting counseling guidance data in the classroom low is good enough. Based on the results of this research, elementary school teachers are able to understand the types of counseling guidance data and data collection techniques. The suggestions from this research are that the research object is expected to be expanded and not limited to just one source.